Design and installation of a mini aquaponic system - Choong, Zi Yew (2022)
Aquaponics is one sort of urban agriculture that integrates the separated aquaculture and hydroponic system into one whole system. As the population increases every year, aquaponics can help to generate various edible foods to prevent food scarcity. However, implementing an aquaponic system can be complicated because it involves integrated design concepts and knowledge related to aquatic life and crops. The system also necessitates well maintenance, including the water quality parameters, fish, and plant care. Hence, the knowledge and experience in handling an aquaponic system will define the successfulness of the system. The study aimed to develop a complete operation of a mini aquaponic system with appropriate design and monitoring. This study reviewed the design and operational aspects such as the types of aquaponics, fish aspects, plant aspects, and water quality parameters. A mini aquaponic system with Deep Water Culture concept were successfully set up at the school laboratory. Two Oranda goldfish and four parsleys were introduced to the mini aquaponic system. System monitoring and operation were conducted for four weeks. The water quality parameters, such as water temperature, pH value, dissolved oxygen, ammonia level, nitrite level, nitrate level, general hardness, and carbonate hardness, were recorded at least twice a week during the 4 weeks. The results indicated that the water quality was maintained at a suitable range for the goldfish and parsleys, except for the low water hardness. Besides, the parsleys had assimilated some nutrients for the root’s development. However, the nutrient deficiency symptoms on parsleys during the late stage of system operation indicates the system is lack of phosphorus and potassium nutrients. Overall, the performance of the aquaponic system was moderate as nutrients supplement and water hardness adjustment are required.